Islamic Education Management Strategy in Responding to the Challenges of Modernity in Tadika Perpaduan Pulau Pinang Malaysia - Meilan Nasir; Abd Rahman (Journal of Innovative and Creativity, 2025)
The study purpose was to examine the management strategies of Islamic education in responding to the challenges of modernity in Malaysia. The focus of the study is on educational practices at Tadika Perpaduan Batu Lancang, Penang, in integrating Islamic values with contemporary educational demands. This research uses a qualitative descriptive approach. Data were collected through observation and interviews conducted during the International Community Service (KPM) and Field Experience Program (PPL) involving students from STIT Al Washliyah Aceh Tengah. The data were analyzed thematically to identify key educational management strategies. The results show that Islamic education in Malaysia adopts an adaptive approach toward modernity. Tadika Perpaduan Batu Lancang integrates spiritual, social, and technological aspects in its educational management, while strengthening students’ moral and character development. These practices are aligned with national education policies, including the J-QAF program. The study concludes that Islamic education management in Malaysia is able to balance religious values with modern educational demands. This integrative approach provides a relevant model for the development of Islamic education in the contemporary global context.